UPAYA MENINGKATKAN KUALITAS PEMBELAJARAN PROSES PEMESINAN MAHASISWA D3 TEKNIK MESIN UNY DENGAN MODEL INTEGRATIF LEARNING - Paryanto, Paryanto (MAJALAH ILMIAH PEMBELAJARAN, 2010)
The purpose of this study was to determine how far the use of an integrative learning model can improve the quality of the learning machining process learning and to know how far Integrative Learning model can enhance students' learning activities and gains..The study design specified in the form of classroom action research design, which is a collaborative research based on problems that arise in the learning activities in class. This research was conducted at Department of Mechanical Engineering Education, Engineering Faculty, , Yogyakarta State University. This method was applied to D3 students who followed machining process course.Base on the research is cuold be concluded that integratif learning model increased students activeness of 26.7%, and students learning gain of 15.4%.